1998
DOI: 10.1046/j.1472-765x.1998.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic growth and survival of Campylobacter jejuni in food and stream water

Abstract: When 40 Campylobacter jejuni isolates from human clinical cases, raw chicken and water were tested, 29 (72·5%) could be adapted to grow on nutrient agar under aerobic conditions. Once adapted, these isolates could grow on repeated aerobic subculture. An aerobically‐grown Camp. jejuni isolate survived almost as well as the same isolate grown microaerophilically in sterile chicken mince at 5 °C, and survival of a cocktail of Camp. jejuni isolates under both atmospheres was comparable at 25 °C. However, at 37 °C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 10 publications
3
23
0
1
Order By: Relevance
“…C. jejuni inoculated in sterile autoclaved ground chicken meat and stored at 4°C in an ambient atmosphere in a covered beaker, or C. jejuni (nalidixic acid-resistant strain) inoculated on raw nonsterile chicken drumsticks in an ambient atmosphere in a tied bag, showed declines of less than 1 log 10 CFU/g and 1 log 10 CFU/ cm 2 , respectively, after 7 days of storage (3). C. jejuni inoculated in sterile autoclaved chicken mince declined approximately 1 log 10 CFU/g over 7 days during aerobic storage in a bag at 5°C (6). C. jejuni has been recovered after 21 days in nonsterile comminuted raw chicken meat stored under ambient conditions in sealed bags stored at 5°C (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. jejuni inoculated in sterile autoclaved ground chicken meat and stored at 4°C in an ambient atmosphere in a covered beaker, or C. jejuni (nalidixic acid-resistant strain) inoculated on raw nonsterile chicken drumsticks in an ambient atmosphere in a tied bag, showed declines of less than 1 log 10 CFU/g and 1 log 10 CFU/ cm 2 , respectively, after 7 days of storage (3). C. jejuni inoculated in sterile autoclaved chicken mince declined approximately 1 log 10 CFU/g over 7 days during aerobic storage in a bag at 5°C (6). C. jejuni has been recovered after 21 days in nonsterile comminuted raw chicken meat stored under ambient conditions in sealed bags stored at 5°C (1).…”
Section: Resultsmentioning
confidence: 99%
“…Campylobacters have an optimal growth temperature range of 37 to 42°C and do not grow below 30°C (15), but C. jejuni has been shown to display physiological activity at 4°C (10) and Campylobacter can survive in water for several weeks at 4°C (23). Counts of C. jejuni on poultry carcasses have been shown to decline during refrigerated storage (29), but studies have shown that a portion of the C. jejuni population survives on raw or cooked poultry samples during refrigeration (1,3,5,6,15,26). Freezing also decreases counts of C. jejuni and reductions of 1 to 3 log 10 in flesh foods stored at Ϫ15 to Ϫ20°C have been observed (29), but C. jejuni does survive during frozen storage in poultry samples (2,15,26).…”
mentioning
confidence: 99%
“…Since raw or undercooked chicken is considered to be an important risk factor for human campylobacteriosis (7,32,40), one would expect that this foodborne pathogen must have the ability to tolerate refrigeration. Many studies demonstrated the remarkable survival of C. jejuni under temperature conditions nonpermissive for growth (3,7,9,11,20), but the mechanisms C. jejuni uses to adapt and control gene expression in response to cold shock are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that C. jejuni can survive on raw and cooked poultry samples during refrigeration at 4°C (8,9,26,38). At 4°C, various biological activities including protein synthesis, oxygen consumption, catalase activity, ATP generation, and motility are still occurring in this bacterium (20,25).…”
mentioning
confidence: 98%
“…Different strains, isolated from different sources, show considerable variability in survival parameters (8). Other environmental factors such as UVB light level, the level of oxygenation, water source and the presence of other microorganisms have been reported to influence C. jejuni survival (5,7,27,36). Korhonen and Martikainen (18,19) showed that survival of C. jejuni was significantly higher in filter-sterilised (0.2-m-filtered) lake water than in untreated lake water or 5.0-m-filtered lake water.…”
Section: Discussionmentioning
confidence: 99%